Expression Patterns of miR‐29b and miR‐148a in Colostrum of Awassi Sheep With Higher Immunoglobulin G Levels - Hüseyin Özkan; Ufuk Kaya; Hasan Hüseyin Keçeli; Ramazan Sertkol; Mustafa Kemal Saribay (Veterinary Medicine and Science)
ABSTRACT This study aimed to investigate the compositional parameters and expression patterns of miR‐29b and miR‐148a in sheep colostrum containing low and high levels of Immunoglobulin G (IgG). Blood and colostrum samples were collected within the first 6 h following birth from 24 pregnant Awassi sheep. On the basis of the determined colostrum IgG levels, low (Low IgG [LIGG], 44.83 ± 4.97 mg/mL) and high (High IgG [HIGG], 80.71 ± 3.31 mg/mL) groups were formed. In addition to measuring colostrum compositional parameters, expressions of miR‐29b and miR‐148a were determined in plasma and colostrum. Although somatic cell score (SCS), pH and electrical conductivity (EC) were higher, fat‐free dry matter (FFDM), protein, lactose and freezing point were lower in HIGG group. Compared to LIGG, miR‐29b was downregulated approximately 5‐fold in the HIGG, whereas miR‐148a was downregulated more than 3‐fold in colostrum. There were negative correlations between colostrum miR‐148a and colostrum IgG, SCS and pH. Colostrum IgG was positively correlated with pH and freezing point and negatively correlated with FFDM, protein and lactose. Area under the curve (AUC) values of SCS, pH, FFDM, protein, lactose, freezing point, EC and miR‐148a (colostrum) were significant. Sensitivity and specificity of pH were 100% and 66.7%, of SCS were 81.8% and 66.7% and of miR‐148a (Colostrum) were 75% and 75% in HIGG and LIGG. According to the results, miR‐29b might be an important molecular target for lamb development, whereas miR‐148a could be a potential biomarker for colostrum quality. Moreover, the study showed that SCS and pH might be useful diagnostic parameters for IgG status because of higher sensitivity rates and AUC values.